VEGETASI TAMAN URBAN SEBAGAI PENYEDIA PAKAN BAGI BEBERAPA TROPHIC GUILD BURUNG HERBIVORA: STUDI TAMAN LAPANGAN BANTENG, JAKARTA PUSAT - Hafidz Prananta Hakamashe; Diah Retno Arumsari; Esti Komariah; Hilmi Febriyani; Intan Febrianty; Nabilah Destiyana; Rahmah Aulia; Wulan Sukmawati; Mohamad Isnin Noer; Agung Sedayu (LPPM Universitas Negeri Jakarta, 2022)
Vegetal food is the most important resource for herbivores. The study of food consumed by bird community in Indonesia, especially in urban environments is needed to provide an overview of the ability of City Parks to support bird communities. The aim was to determine the urban park vegetation in the Lapangan Banteng park as a potential food source for urban birds, especially frugivores, nectarivores and granivores. The study was conducted in September until December 2018 . Data were analyzed using Rstudio and ImageJ. The results showed that there were 7 species of birds consisting: four species of granivores (Passer montanus, Streptopelia chinensis, Lonchura punctulata, and Pycnonotus aurigaster) and three species of frugivores (Psittacula alexandri, Dicaeum trochileum, Treron vernans) which were observed to use plants as food resource Lapangan Banteng park. Birds used 30% of trees (Syzygium polyanthum, Melaleuca leucadendra, Ficus benjamina) and 70% of herbaceous ground cover (Arachis pintoi., Phoenix sp., Pennisetum purpureum, Axonopus compressus, Cynodon dactylon, Cyperus rotundus, and Eleusine indica). The availability of sufficient natural food in nature will have an impact on both bird conservation and the environment. The availability of natural food will improve bird conservation and ensure the sustainability of urban biodiversity.